Korelasi Konsumsi Sidaguri dengan Kadar Asan Urat Darah - Suprianto Suprianto; Adek Chan; Joko Wibowo; Samran; Sumardi; Debi Meilani (Yayasan Penelitian dan Inovasi Sumatera, 2025)
Background: Hyperuricemia as an indicator of increased blood uric acid. The prevalence rate in Indonesia is not recorded with certainty. However, the prevalence of gout reached 655,745 people out of 238,452,952 people in Indonesia, ranking first in Southeast Asia. Sidaguri flavonoids have inhibitory power against Xanthine Oxidase so that they can reduce uric acid. Objective: The study was aimed at detecting the effect and correlation of Sidaguri capsule consumption (Sida rhombifolia L) on reducing uric acid in patients. Method: The study was conducted Pretest and Posttest on 22 patients with hyperuricemia with the Easy Touch GCU Instrument. Results: The results showed that the average uric acid level before the intervention was 8.37 mg/dL and after the intervention was 6.57 mg/dL. Conclusion: Sidaguri capsules have an effect on reducing uric acid levels in patients